Implementasi Kebiasaan Membaca Al-Quran dalam Meningkatkan Pemahaman Ajaran Islam Siswa MI Al Urwatul Wustqo 1 Bulurejo Diwek Jombang - Eny Fatimatuszuhro Pahlawati; Roikhatul Jannah; Muhammad Ayang Amrulloh (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to analyze the influence of the habit of reading the Qur'an on students' understanding of Islamic teachings at MI Al-Urwatul Wutsqo 1, located in Bulurejo Village, Diwek District, Jombang Regency. The background of this research is based on the importance of cultivating the habit of reading the Qur'an as an integral part of character and spiritual education that contributes to students’ deep comprehension of Islamic values. This study employs a descriptive qualitative approach using data collection techniques such as observation, interviews, and documentation. The results show that the regular practice of reading the Qur'an implemented at MI Al-Urwatul Wutsqo 1 positively impacts students' understanding of Islamic teachings. Students who consistently engage in reading the Qur'an demonstrate enhanced religious awareness, discipline, noble character, and better understanding of Islamic Education subjects. Activities such as daily Qur'anic recitation (tadarus) and memorization programs help shape students into religious and morally upright individuals. Therefore, the habit of reading the Qur'an proves to be an effective means of supporting Islamic education and fostering Islamic character in students. Keywords : Habits,Reading the Qur'an, Islamic Teachings, Islamic Education, MI Al-Urwatul Wutsqo 1